Autoeficácia e apoio social de mães de recém-nascidos prematuros em unidade de cuidado neonatal - Pinheiro, Sarah Rayssa Cordeiro Sales (2019)
The objective of the study was to analyze the level of maternal self-efficacy perceived about the care of the baby and its relation with the social support of mothers of preterm infants in the Neonatal Care Unit. Epidemiological study of the transverse type, carried out in reference maternity hospital in Fortaleza. The population was composed of 120 mothers of premature newborns in hospital admission. The sample was constructed for convenience, from the continuous admission of the binomials in the period from June to September 2018. Three instruments were used for the collection: sociodemographic, Perceived Maternal Self-efficacy Scale and Social Support Scale MOSS. For statistical analysis, the Mann-Whitney U. Test, Kruskal Wallis test and Spearman correlation were used. The study was approved by the ethics committee under opinion 2,683,635. Most of the women were between the ages of 20 and 30, they came from the capital or metropolitan region, had more than 9 years of study, had a partner, did not work in paid employment and had income of 1 to 2 salaries. A little more than half of the mothers were multiparous, they performed prenatal care, but few participated in groups of pregnant women. The statistical tests show a positive correlation of Self-efficacy with parity and years of study of the mothers. However, women with up to 8 years of schooling presented higher levels of parental confidence. The mean score on the Maternal Self-efficacy scale was 59.1, considered moderately satisfactory, with factor 3 - behavior reading - with the lowest mean. In relation to social support, the average score was 74.3, considered high. The dimensions with lower averages were Emotional Support and Positive Social Interaction Support. (P = 0.002), Emotional (p = 0.002), Information (p = 0.003), Affective (p = 0.003) and Positive Social Interaction (p = 0.002) = 0.015) - also demonstrated a significant correlation with Perceived Maternal Self-Efficacy. Thus, parity, years of study and social support and their dimensions have been predictors of Perceived Maternal Self-Efficacy. The study was relevant because, when analyzing maternal self-efficacy and its relation with social support, the nurse can promote care from a perspective that takes into account the mothers' prior knowledge and their support network from a care plan that involves the educational component directed to the real needs, reducing expenses and minimizing future intercurrences.